2005
DOI: 10.1093/ajcn.82.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Plasma kinetics of lutein, zeaxanthin, and 3-dehydro-lutein after multiple oral doses of a lutein supplement

Abstract: Long-term supplementation with 4.1 and 20.5 mg lutein as beadlets increased plasma lutein concentrations approximately 3.5- and 10-fold, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…The conversion of 3′-dehydro-lutein from lutein was 6%. Thurman et al have also shown this to occur in humans (Thurmann et al, 2005). However, our study is unique in that this conversion was measured without the interference of 3′-dehydro-lutein possibly formed from zeaxanthin (Hartmann et al, 2004).…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…The conversion of 3′-dehydro-lutein from lutein was 6%. Thurman et al have also shown this to occur in humans (Thurmann et al, 2005). However, our study is unique in that this conversion was measured without the interference of 3′-dehydro-lutein possibly formed from zeaxanthin (Hartmann et al, 2004).…”
Section: Discussionmentioning
confidence: 51%
“…The separation of (3R,6′S)-and (3R,6′R)-3′-dehydro-lutein, lutein and zeaxanthin on chiral-phase HPLC in comparison to normal-phase (Si-60) HPLC is shown in Figure 4. We first applied this chiral-phase separation successfully to the analysis of 3′-dehydro-lutein in human plasma (Höller et al, 2005) out of the LUXEA-study Hartmann et al, 2004;Thurmann et al, 2005). In the recent work, we coupled the chiral separation to HR-MS detection, which enabled us to establish the exact molecular masses of the carotenoids in the chromatograms investigated.…”
Section: Chiral-phase Hplc Analysis and Hr-ms Detectionmentioning
confidence: 99%
See 3 more Smart Citations